Partai Politik Dalam Perspektif Regulasi Dan Implementasi Keterwakilan Perempuan (Studi Pada Partai PKB, PDI-P, GOLKAR Kota Probolinggo) - Veronica Sri Astuti Nawangsih; Husni Mubaraq; Binti Nasikhatul Ummatin (LPPM Politeknik Pratama, 2023)
Political parties as a forum that accommodates and distributes people's aspirations are an important component in the advancement of gender equality in Indonesia, as we know that gender issues are many unresolved problems, women's involvement in political participation in parties has become one of the the key to successful implementation of gender in Indonesia.